2009
DOI: 10.1007/s10800-009-9968-1
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of tin oxide, iridium and iridium oxide films by metal-organic chemical vapor deposition for electrochemical wastewater treatment

Abstract: In this research, the specific electrodes were prepared by metal-organic chemical vapor deposition (MOCVD) in a hot-wall CVD reactor with the presence of O 2 under reduced pressure. The Ir protective layer was deposited by using (Methylcyclopentadienyl) (1,5-cyclooctadiene) iridium (I), (MeCp)Ir(COD), as precursor. Tetraethyltin (TET) was used as precursor for the deposition of SnO 2 active layer. The optimum condition for Ir film deposition was at 300°C, 125 of O 2 /(MeCp)Ir(COD) molar ratio and 12 Torr of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…To briey conclude sub-Section 4.2, it can be stated that in all studied CVD options (MOCVD and P-CVD) as well as ALD option, the deposited iridium thin lms revealed localized initial nucleation on the studied surfaces followed by more or 66 have studied iridium coatings grown by metal-organic chemical vapor deposition in a tubular hot-wall CVD reactor using (methylcyclopentadienyl)(1,5-cyclooctadiene)iridium, (Ir(COD)(MeCp)), as a precursor in the presence of H 2 or O 2 , see Table 5. This precursor was selected because it is an air-stable compound that can be used as liquid source that permits a constant vapor phase delivery rate.…”
Section: 25mentioning
confidence: 95%
See 1 more Smart Citation
“…To briey conclude sub-Section 4.2, it can be stated that in all studied CVD options (MOCVD and P-CVD) as well as ALD option, the deposited iridium thin lms revealed localized initial nucleation on the studied surfaces followed by more or 66 have studied iridium coatings grown by metal-organic chemical vapor deposition in a tubular hot-wall CVD reactor using (methylcyclopentadienyl)(1,5-cyclooctadiene)iridium, (Ir(COD)(MeCp)), as a precursor in the presence of H 2 or O 2 , see Table 5. This precursor was selected because it is an air-stable compound that can be used as liquid source that permits a constant vapor phase delivery rate.…”
Section: 25mentioning
confidence: 95%
“…Ir thin lms were deposited on tungsten 65 and silicon 66 substrates by thermal decomposition of Ir(COD)(MeCp) either in the presence of H 2 or O 2 . The growth was carried out in a horizontal hotwall MOCVD reactor under reduced pressure and low temperature (350-500 C).…”
Section: 25mentioning
confidence: 99%
“…Besides, the cracks or surface stresses entrap air and gas bubbles, prevent effective control of the solution, and result in a poor coating process. Generally, the electrolyte system is not under the control of the designer, but he can perform various actions to reduce problems and complications induced by the other factors and contribute to an effective coating process (3,9,44,65,92,95,96,107,124,(166)(167)(168)(169)(170)(171)(172)(173)(174)(175).…”
Section: Designmentioning
confidence: 99%
“…Although, the current density might not affect on the kinetic of surface electrochemical oxidation of organic pollutant, it also enhances the production of bulk chemicals, which may contribute to the degradation process through parallel reaction schemes. Klamklang (Klamklang, 2006, Klamklang, 2007and Klamklang et al, 2010 has found that increasing current density from 5 to 10 mA/cm 2 , leads to less degradation rate of oxalic acid by electrochemical oxidation. This behavior is characteristic of mass transfer-controlled processes (Kesselman, 1997).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The G-bag approach, which uses a bag of absorbent to capture the pollutants and degrade the pollutants with the immobilized microorganisms on the absorbent, seems to be a good alternative only if the system can be designed as simple and free from fouling (Chen et al, 2000). In this work, the treatment of restaurant wastewater by electrochemical incineration is obtained with continuous electrochemical oxidation system described elsewhere Klamklang (Klamklang, 2006, Klamklang, 2007and Klamklang et al, 2010. A simple three-electrode electrochemical reactor with 18 ml of capacity with using Ti/SnO 2 electrodes as anode, the 316L stainless steel was used as cathode.…”
Section: Electrochemical Incineration For Restaurant Wastewater Treatmentioning
confidence: 99%